Natural capitalism creating the next industrial revolution - Hawken, Paul; Lovins, Amory B.; Lovins, L. Hunter 1950- (Little, Brown, 1999)
"In the book, these durable, practical, and stunningly profitable principles are synthesized for the first time into the foundations for a system called natural capitalism."--BOOK JACKET